From folding to function: complex macromolecular reactions unraveled one-by-one with optical tweezers. Issue 1 (16th April 2021) - Heidarsson, Pétur O.; Cecconi, Ciro
Abstract: Single-molecule manipulation with optical tweezers has uncovered macromolecular behaviour hidden to other experimental techniques. Recent instrumental improvements have made it possible to expand the range of systems accessible to optical tweezers. Beyond focusing on the folding and structural changes of isolated single molecules, optical tweezers studies have evolved into unraveling the basic principles of complex molecular processes such as co-translational folding on the ribosome, kinase activation dynamics, ligand–receptor binding, chaperone-assisted protein folding, and even dynamics of intrinsically disordered proteins (IDPs). In this mini-review, we illustrate the methodological principles of optical tweezers before highlighting recent advances in studying complex protein conformational dynamics – from protein synthesis to physiological function – as well as emerging future issues that are beginning to be addressed with novel approaches.